Ingestive behavior of Nellore cattle confined during the growing phase in different shading strategies - Durães, Hellén Felicidade; Carvalho, Cinara da Cunha Siqueira; Gonçalves, Maria Cecília Magalhães; Ruas, José Reinaldo Mendes; Monção, Flavio Pinto; Rocha Júnior, Vicente Ribeiro; Gomes, Virgílio Mesquita; Valentim, Jean Kaique (Acta Scientiarum. Animal Sciences, 2025)
The study evaluated different shading strategies on the ingestive behavior of confined Nellore cattle during the growing phase. The experiment was conducted in the semi-arid region of Minas Gerais, Brazil, with 225 Nellore cattle (10 months old, 240 kg body weight). A completely randomized design was used with three treatments: no shading (full sun), natural shading (trees), and artificial shading, with 75 animals per group. Climatic variables were recorded, and feeding, ruminating, and idling behaviors were observed every 15 minutes for 24 hours. The full-sun environment was the most uncomfortable, with the highest air temperatures recorded between 12:00 a.m. and 2:50 p.m. Animals under natural shading showed higher feeding frequency, improved feeding efficiency, and greater daily weight gain, resulting in higher final weights. A significant difference (p < 0.05) in air temperature was found among treatments, with the highest value under full sun (29.3°C). Relative humidity and air velocity did not differ significantly. Natural shading improved the environment, leading to better zootechnical performance. The study concluded that providing natural shade for confined Nellore cattle improved ingestive behavior, increased feeding frequency and efficiency, and enhanced weight gain. This strategy is recommended for better cattle management and welfare in semi-arid regions.